Analisis Konten Youtube Sebagai Media Belajar Berbasis E-Learning Pada Materi Pecahan - Aulia, Rahmawati; Sucipto, Lalu; Kinasih, Indira Puteri (Jurnal of Math Tadris, 2022)
The purpose of this study is to describe the extent to which the concept of fractions is presented in learning video content on four channels in Indonesia including the Le Guru Les, Sigma Smart Study, Math Class Ku, and Pras Academy channels. This study uses a qualitative research approach using content analysis methods. Data were collected through analysis activities on four aspects, namely content aspects, presentation aspects, graphic aspects, and language aspects which contained several indicators in each of these aspects. The results of the study indicate that the Math Class Ku channel can help with learning difficulties in mathematics with fractions because it starts from the content aspect that meets the basic competencies (KD) of the 2013 curriculum so that the learning objectives for fractions material in class VII SMP are achieved, although there are still sub-chapters that have not been discussed. In addition, the presentation and graphic aspects consist of various kinds of attractions in the form of interactive stimuli, pictures, and illustrations in helping students understand fractional material and only two non-standard words were found. The second order of the Sigma Smart Study channels from the aspect of content there is still a KD that is not fulfilled but contains several pictures and illustrations of fractions, but there are clipped sounds and the use of some words is not standard. The third order of the Pras Academy channels from the aspect of content has fulfilled the KD but is more towards solving sample questions and using several solutions. The background of this channel is still monotonous because it lacks the use of attractiveness and there are sentences that are not effective in helping students understand the fraction material. And the fourth channel is Le Guru Les, which fulfills the KD but has not been detailed in discussing the basic concepts of fractions and still really needs interactive stimuli, pictures and illustrations and there are still some ineffective use of words and sentences in helping students understand fraction material.